Design of Slag System for FB2 Heat-resistant Steel Electroslag Remelting and Its Effect on Element Loss - Li Longfei, Niu Chengzhou, Wang Ning, Wang Chunhui, Lin Tengchang, Zhou Xiaozhou (Teshugang)
Based on the principle of low eutectic point， a new basic slag system for electric slag remelting of FB2 heat-resistant steel was designed and calculated by FactSage software. The effects of traditional slag system 69.65% CaF2-29.85% Al2O3-0.5% B2O3 （1#） and new slag system 50.4% CaF2-26.5% CaO 19.6% Al2O3 3% MgO 0.5% B2O3 （2#） on the content changes of easily oxidizable elements in steel were compared and investigated using slag-metal equilibrium and 10 kg electroslag remelting experiments.The results show that ， compared with the traditional slag system， the melting temperature， viscosity and resistivity at different temperatures of the new design slag system are lower.When the activity of Al2O3 component in the slag is high and the activity of SiO2 and B2O3 components is at a low level， Si and B probably will react with low oxygen potential Al2O3 between the slag and the metal based on thermodynamic calculations. The content of w［B］ in the reaction equilibrium between the two slag systems and FB2 steel is 0.001 9% ，0.004 3%， respectively. In both slag series， Si and B elements will be burned and Al is increased in steel during slag-metal equilibrium and electroslag remelting smelting. In 2# slag series， the element fluctuation is small， and the variation range of element content decrease significantly after 60 min of slag-metal equilibrium time. In contrast， the change in element content in the electric slag ingot after remelting is smaller.